An Injectable Hydrogel Bioimplant Loaded with Engineered Exosomes and Triple Anti-Tuberculosis Drugs with Potential for Treating Bone and Joint Tuberculosis - Huang J; Li H; Mei Y; Yi P; Ren Y; Wang Y; Han L; Tang Q; Liu D; Chen W; An Y; Hu C (International Journal of Nanomedicine)
Jiayan Huang,1,* Han Li,2,* Yuting Mei,1 Pengcheng Yi,1 Yunyao Ren,1 Yunjuan Wang,3 Limei Han,1 Qiusha Tang,3 Dongfang Liu,3 Wei Chen,4 Yanli An,5 Chunmei Hu1 1Department of Tuberculosis, the Second Hospital of Nanjing, Affiliated to Nanjing University of Chinese Medicine, Nanjing, People’s Republic of China; 2Department of Pharmacy, Central Hospital of Guangdong Provincial Nongken, Zhanjiang, Guangdong, People’s Republic of China; 3Medical School of Southeast University, Nanjing, People’s Republic of China; 4Department of Clinical Research Center, The Second Hospital of Nanjing, Nanjing University of Chinese Medicine, Nanjing, People’s Republic of China; 5Nurturing Center of Jiangsu Province for State Laboratory of AI Imaging & Interventional Radiology (Southeast University), Center of Interventional Radiology & Vascular Surgery, Department of Radiology, Medical School, Zhong da Hospital, Southeast University, Nanjing, Jiangsu People’s Republic of China*These authors contributed equally to this workCorrespondence: Chunmei Hu, Department of Tuberculosis, the Second Hospital of Nanjing, Affiliated to Nanjing University of Chinese Medicine, Zhongfu Road 1-1, Yijiangmen Street, Nanjing, Jiangsu Province, 210009, People’s Republic of China, Email njyy003@njucm.edu.cnPurpose: Treatment for bone and joint tuberculosis (BJTB) is challenging due to its refractory and recurrent nature. This study aimed to develop a bioimplantable scaffold with osteoinductive and antituberculosis characteristics to treat BJTB.Methods: This scaffold is built on oxidized hyaluronic acid and carboxymethyl chitosan hydrogel mixed with hydroxyapatite as a bone tissue engineered material. In order to make the scaffold have the biological activity of promoting tissue repair, the engineered exosomes (Exoeng) were added innovatively. In addition, drug-loaded liposomes equipped with an aldehyde group on the surface are cross-linked with the amine group of the hydrogel skeleton to participate in the Schiff base reaction.Results: The designed scaffold has characteristics of self-healing and injectability exhibit excellent anti-tuberculosis and promoting bone repair activities. Exoeng strongly stimulates cellular angiogenesis and osteogenic differentiation. The liposomes coated in hydrogel can release three kinds of anti-tuberculosis drugs smoothly and slowly, achieving a long term anti-tuberculosis.Conclusion: The composite bio-scaffold shows good tissue repair and long-term anti-tuberculosis abilities, which expected to provide a viable treatment plan for bone-related BJTB.Keywords: hydrogel scaffolds, engineered exosomes, triple anti-tuberculosis drugs loaded, bone and joint tuberculosis, therapy